Revisiting the corporate image through service quality and relationship marketing: an empirical evidence from Malaysian and Saudi Arabian Takaful customers. Issue 6 (3rd August 2021) - Abdur Rehman, Mohsin; Khan, Sadaf; Osman, Ismah; Aziz, Khurram; Shams, Ghazal
Abstract : Purpose: This study aims to test a proposed model based on a combination of the relationship marketing and service quality dimensions as predictors of corporate image and customer loyalty via corporate reputation in the Takaful context. More importantly, this study compares the Takaful operators' services with the perceived service quality and the relationship marketing from the Malaysian and Saudi Arabian customers' viewpoint. Design/methodology/approach: A survey-based study was conducted through a questionnaire, and the data was collected from Takaful customers (362 Saudi Arabian and 350 Malaysian customers) through an online survey. Structural equation modelling is used to test the proposed model. Besides, the perception of Takaful customers between Saudi Arabia and Malaysia is compared through a multi-group analysis. Findings: The results from the Malaysian context reveal that positive perceptions of service quality PAKSERV dimensions (personalization, reliability and tangibility) and positive perceptions of relationship marketing dimensions (Islamic ethical behaviour and structural bonds) have a significant influence on the corporate image. Alternatively, in the Saudi Arabian context, results have shown that the positive perceptions of service quality PAKSERV dimensions (assurance and reliability) of service quality and the positive perceptions of the relationship marketing dimensions (Islamic ethical behaviour, structural bonds and financial bonds) have a significant influence on the corporate image. The differences in both countries' results can also enhance the corporate image on corporate reputation, merely in Malaysia. By contrast, corporate reputation is deemed a significant predictor of customer loyalty, represented as valid for both contexts. Research limitations/implications: The proposed research model tested in Takaful Malaysian and Saudi Arabian can be replicated in other contexts – in terms of country and industry. Moreover, the current study reveals the crucial role of corporate image in forming corporate reputation. Future research could be focussed on the importance of other emotional or affective variables that may be involved in determining corporate reputation. Finally, future studies can be carried with another cultural perspective to have more diversified socio-economic implications. Practical implications: It is suggested that Takaful operators from both Malaysia and Saudi Arabia need to put maximum effort towards customer loyalty by bringing both the dimensions of service quality and the relationship marketing in compliance with the principles of Islamic business transaction. The findings of the specific dimensions of service quality and relationship marketing will contribute to customers' perceptions of corporate image and reputation in the Takaful industry. Originality/value: The present study tested a blended facet of customer's overall experience through service quality (PAKSERV) and customer service provider connectivity (relationship marketing) to predict the corporate image of the highly growing financial marketplace (Takaful). Contextually, this study contributes to delineating the factors (corporate reputation) affecting customer loyalty rather than a customer satisfaction tradition. Significantly, Saudi Arabia and Malaysia were chosen for this study, as they are currently the two fast-growing markets for Islamic financial services, especially with regards to the Takaful products and offerings.